Transmission of dengue hemorrhagic fever in an age structured population - P. Pongsumpun (2018)
The influence of age structure in the human population in the susceptible-infected recovered (SIR) model used to describe the transmission of Dengue hemorrhagic fever (DHF) is studied. The human population is separated into an adult class and juvenile class with the transmission of the disease being different in the two classes. Two equilibrium states are found and the condition for stability of one of these states, the disease free state, is established. The stability of the endemic state of this model is discussed. A simplified version of the model, one in which no adults become sick, is introduced. The conditions for the stability of the endemic state of this latter model are determined. Numerical calculations show that age structure in the simplified model reduces the periods of oscillations in the susceptible human population, the infected human population, and the infected mosquito population and the tightness of the spiraling into the endemic equilibrium state. © 2003 Elsevier Science Ltd. All rights reserved.